Effects of Information Literacy Skills on the Utilisation of Library Information Resources among Undergraduate Students in Kano State - MABRUKA, ABUBAKAR ABBA; HARANDE, YAHYA IBRAHIM (MiddleBelt Journal of Library and Information Science, 2020)
Studies have found that, apart from lack of basic information literacy skills on the part of the students, there are problems emanating from the management such as dearth of information resources, lack of adequate reading space, bad policy, etc. which could impede on undergraduate students’ use of information resources. There is the need for an investigation into the nature of this problem among Nigerian students. This study therefore, investigates legitimacy of information literacy skills (ILS) and the use of information resources by researchers. Undergraduate students of universities in Kano State were used as the population for the study. The objectives include to find out understanding about ILS among the undergraduate students and to determine the level of utilization of information resources by undergraduate in universities in Kano State. Quantitative method data was employed and analysed using inferential statistics through Statistical Package for Social Science (SPSS). The study revealed that majority of the students has high level of information literacy skills and utilization of information resources. The study also found them use information resources for their academic activities to a greater extent. The study concludes that despite the challenges faced by these students, their information literacy skills are high. The study recommends the need to make libraries comfortable and more convenient to make them more interesting places to the students. Sensitization on the use of ILS to students is also recommended for the improvement of their academic pursuit.